EFEKTIVITAS PELATIHAN KECAKAPAN HIDUP (LIFE SKILLS) TERHADAP SKOR KECERDASAN EMOSI PADA REMAJA Studi di SMAN 1 Tuntang Kabupaten Semarang - Yunita Sumantri (FKU 16 UMY 061, 2016)
Background : Adolescents are generation that are potential for their nation so they should be prepared as best as possible to face demographic dividend in the future. One of the key that those adolescents should have is emotional intelligence in order to become the nation's next generation with a good quality Weakness in emotional intelligence will widen the risk spectrum of deprsession, violence, eating disorders and drugs abuse. Therefore, an intervention to increase the emotional intelligence of adolescents, such as life skills training, is needed. Objective : The purpose of this research is to know the effectiveness of life skills training towards emotional intelligence score in adolescents. Method : This research was a quasi experimental study using pre-test and post-test control group design. Seventy six students of SMAN 1 Tuntang that fit the inclusion and exclusion criterias were chosen to participate in this study and then they were divided into intervention group which was the group that received a life skills training and control group which was not given any intervention as a comparator. The data were obtained from emotional intelligence questionnaire which was filled by the participants before and after given the life skills training throughout 2 weeks. The module of life skills training used in this study was a training guide published by The Directorate of Mental Health from Department of Health, Republic of Indonesia consisting of how to manage stress, increasing self-esteem, and overcome pressures.